Analisis Modal Psikologis dan Lingkungan Kerja Terhadap Organizational Citizenship Behavior (OCB) melalui kepuasan kerja Pada Pegawai Dinas Kelautan dan Perikanan Provinsi Yogyakarta - Wibowo, Fattah Ario (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2024)
Psychological capital does not have a positive and significant effect on Organizational Citizenship Behavior (OCB), Work environment has a positive and significant effect on Organizational Citizenship Behavior (OCB), Psychological capital has a positive and significant effect on job satisfaction, Work environment has a positive and significant effect on job satisfaction, Satisfaction work has a positive and significant effect on Organizational Citizenship Behavior (OCB), Job satisfaction has a positive and insignificant effect as a mediating variable between psychological capital and Organizational Citizenship Behavior (OCB), Job satisfaction has a positive and insignificant effect as a mediating variable between the work environment and Organizational Citizenship Behavior (OCB). Keywords: Psychological capital, work environment, OCB